Comprehension Skills: What is the Best Way to Absorb Meaning? - Bryan Hahn (Journal of Interdisciplinary Sciences)
The study aims to determine if reading a sample TOEFL exam three times improves comprehension compared to intensively reading the same material. Two groups of students were tested on the reading section of a sample TOEFL exam, with one group (n=18) that read the literature three times while the other group (n=13) read it once. An independent t-test compared the exam scores and did not show any significant difference. The scores for those who read the material three times were virtually the same compared to the group that read the same material once intensively. Another independent t-test was also conducted comparing the scores of the first group that read the literature three times versus the same group that read it once. The results were significant but had the opposite result of the expected outcome. In other words, scores were higher after reading the material once which goes against long established academic literature.